Boundary layer flow of dusty williamson fluid with variable viscosity effect over a stretching sheet - Nur Syamilah, Arifin; Abdul Rahman, Mohd Kasim; Syazwani, Mohd Zokri; Mohd Zuki, Salleh (Semarak Ilmu Publishing, 2021)
Numerical investigation of the boundary layer flow of Williamson fluid with the presence of dust particles over a stretching sheet is carried out by taking into account the variable viscosity effect and Newtonian heating boundary condition. The genuinely two-phase flow model which has been proved to be compatible to present the mutual relationship between non-Newtonian fluid and solid particles is considered in this present study. To be precise, the governing equations are initially transformed into ordinary differential equations through formulation process before proceeding further with the numerical computation by using Keller-box method. The resulting equations are then programmed in Matlab software. The obtained numerical results are validated with existing study found in open literature and a good agreement is achieved. The influence of pertinent parameters on velocity and temperature profiles, skin friction coefficient together with Nusselt number is presented in graphical and tabular forms. Results revealed that the increasing Williamson parameter decreases the fluid velocity of both fluid and dust phases. It is expected that the present numerical results could conceivably help in predicting the boundary layer problem arising in two-phase flow in the future.